The impact of regional cooperation on the development of Philippines- Malaysia bilateral relations, 1957-2010 - Rammani Karupiah (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article examines the impact of regional alliances in the shaping of Philippines-Malaysia relations. Philippines-Malaysia bilateral relations have been predominantly driven by the Philippines’ Sabah claim. This is a long-held misconception that warrants a reevaluation by considering other driving factors such as regional cooperation, which has played a big part in Philippines-Malaysia relations which is indeed the novelty of this article. A shared vision by Philippine and Malaysian leaders was the key factor in the formation of the ASA and ASEAN. Their involvement in initiating regional cooperation began when President Garcia met Tunku Abdul Rahman, the Malaysia Prime Minister, in Manila in January 1959. This effort led to the formation of the Association of South-East Asia (ASA) in July 1961 which was the first regional body established in Southeast Asia. Garcia and Tunku shared a vision to establish a regional organization to counter communist threats and enhance mutual security in the region. The establishment of ASA has been a factor in the establishment of ASEAN. Through ASEAN, concepts such as musyawarah and muafakat are accepted by the Philippines and Malaysia to resolve the Sabah issue. This article also discusses the geopolitical situation in the region during the 1960s and beyond, influenced by the spread of communist ideology was an important factor for non-communist countries in Southeast Asia to stay united. This article will explore the extent to which commitment to regional alliances such as ASA, MAPHILINDO (Malaysia, Philippines, Indonesia) and ASEAN emerged as driving forces in the development Philippines-Malaysia bilateral relations. Philippines and Malaysia have cooperated in various regional initiatives which have generated many and tremendous mutual benefits. Successful cooperation and collaboration in many areas brought positive impacts and significance in bilateral ties which have been overlooked in other studies. Furthermore, this article also contributes to the understanding that regional cooperation was and is the cornerstone of the Philippines’ and Malaysia’s foreign policy direction.